Patch Antenna for Measuring the Internal Temperature of Biological Objects Using the Near-Field Microwave Radiometric Method; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Ubaychin (Ubaichin) A. V. Anton Viktorovich; Bespalko (Bespal'ko) A. A. Anatoly Alekseevich; Filatov A.; Alexeev E.; Zhuk G. (2016, 2016)
Title screen